Pelatihan Penulisan Artikel Berorientasi Publikasi Sinta Di SDN 2 Rumak - Anwar, Khairil; Lukman, Lukman; Suparman, Suparman; Y.P, Martoni; Aminudin, Aminudin; J, Raudatul; S.P, Herliana; M, Intan (Abdimas Mandalika, 2025)
Abstract: The ability to write scientific articles is important for educators, as a way to develop self-quality. This activity aims to improve the skills of writing research results in accordance with the rules of reputable national journals. This training was carried out by explaining theoretically, discussing, simulating, and sharing experiences. The activity was attended by 14 teachers of SDN 2 Rumak. Before and after the training, an assessment was carried out to compare the increase in understanding and skills of the participants. The results of the analysis showed an increase in understanding in writing scientific articles according to an OJS template, article components, and their systematics. Through this training, participants can understand the format and structure of articles according to publishing standards. In addition, monitoring and evaluation of participant performance, it was seen that teachers were enthusiastic in writing drafts of scientific papers, actively asking questions, and discussing. This activity is expected to help teachers develop writing skills and creativity so that they can disseminate their knowledge through article publication.Abstrak: Kemampuan menulis artikel ilmiah merupakan hal penting bagi  pendidik, sebagai cara mengembangkan kualitas diri. Kegiatan ini bertujuan untuk meningkatkan keterampilan menulis hasil penelitian yang sesuai dengan aturan jurnal nasional bereputasi. Pelatihan ini dilakukan dengan menjelaskan secara teoritis, diskusi, simulasi, dan berbagi pengalaman. Kegiatan dihadiri oleh 14 orang guru SDN 2 Rumak. Sebelum dan sesudah pelatihan dilakukan penilaian untuk membandingkan peningkatan pemahaman dan keterampilan peserta. Hasil analisis menunjukkan adanya peningkatan pemahaman dalam penulisan artikel ilmiah sesuai dengan suatu template OJS, komponen artikel, dan sistematikanya. Melalui pelatihan ini, peserta dapat memahami format dan struktur artikel sesuai standar penerbitan. Selain itu, monitoring dan evaluasi terhadap unjuk kerja peserta, terlihat para guru antusias dalam melakukan penulisan draf karya ilmiah, aktif bertanya, dan berdiskusi. Kegiatan ini diharapkan dapat membantu guru dalam mengembangkan keterampilan dan kreativitas menulis sehingga dapat menyebarluaskan ilmu pengetahuannya melalui publikasi artikel.